Metamorphoses of the vampire in literature and film cultural transformations in Europe, 1732-1933 - Butler, Erik 1971- (Boydell & Brewer, 2010)
For the last three hundred years, fictions of the vampire have fed off anxieties about cultural continuity. Though commonly represented as a parasitic aggressor from without, the vampire is in fact a native of Europe, and its 'metamorphoses,' to quote Baudelaire, a distorted image of social transformation. Because the vampire grows strong whenever and wherever traditions weaken, its representations have multiplied with every political, economic, and technological revolution from the eighteenth century on. Today, in the age of globalization, vampire fictions are more virulent than ever, and the monster enjoys hunting grounds as vast as the international market. 'Metamorphoses of the Vampire' explains why representations of vampirism began in the eighteenth century, flourished in the nineteenth, and came to eclipse nearly all other forms of monstrosity in the early twentieth century. Many of the works by French and German authors discussed here have never been presented to students and scholars in the English-speaking world. While there are many excellent studies that examine Victorian vampires, the undead in cinema, contemporary vampire fictions, and the vampire in folklore, until now no work has attempted to account for the unifying logic that underlies the vampire's many and often apparently contradictory forms. Erik Butler holds a PhD from Yale University and has taught at Emory University and Swarthmore College. His publications include 'The Bellum Gramaticale and the Rise of European Literature' (2010) and a translation with commentary of 'Regrowth' ('Vidervuks') by the Soviet Jewish author Der Nister (2011)
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Geschichte 1732-1933; Geschichte 1918-1933; Geschichte; Vampires in literature; Vampires / History; Horror tales, European / History and criticism; European fiction / History and criticism; Vampire films / History and criticism; Social change in literature; Literature and society / Europe / History; Vampir; Film; Weimarer Republik; Literatur; Europa; Deutschland